Viral Nervous Necrosis and Vibriosis in Grouper Fish: A Case Study - Gian Suryanatha Hartawan; Uun Yanuhar; Muhammad Musa; Amira Baihani; Yusuf Arif Wahyudi; Choirul Huda; Nico Rahman Caesar (Journal of Aquaculture and Fish Health, 2023)
Viral Nervous Necrosis (VNN) and Vibriosis are contagious diseases that can affect grouper fish from the larval to adult stages and cause significant economic losses for farmers. The owner brought the sunuk grouper to BKIPM Mataram to determine the fish's health. Since the grouper arrived at the floating net cage, the owner reports it has sustained bodily injuries. The grouper is separated from the healthy fish and placed in the area where the sick fish are. During maintenance, the fish exhibits a decrease in appetite, wounds on the mouth, operculum, and body from the head to the tail, low mobility, and swimming upside-down. The physical examination revealed that the fish was swimming limply in an inverted position and had lesions on various body parts. According to virological and bacteriological laboratory tests, the sunuk grouper infected with Vibriosis and VNN can be affected by the condition of fish that have been sick since they first arrived. Also, stress, contact with infected fish, and a decreased appetite result in sunuk grouper contracting the disease. Due to a disease, a fish's immune system does not function optimally. This condition makes sunuk susceptible to several infectious diseases.